Full day school education: pros, cons, and its impact on the social psychology of generation alpha (A phenomenological study in Tuban regency) - Hidayati, Ninik; Ngainin, Nurul; Salamah, Ummidlatus (Institute of Computer Science (IOCS), 2025)
This study examines the implementation of full day school, the diverse perspectives surrounding it, and its psychological implications for Generation Alpha in Tuban Regency. Employing a qualitative phenomenological approach, data were collected from teachers, students, and parents across five Islamic elementary schools. The study found that full day school is implemented through a structured combination of academic learning, religious activities, and character development. Its novelty lies in revealing how extended school hours shape the social psychology of Generation Alpha particularly their self-confidence, discipline, responsibility, and patterns of social interaction. While the system offers notable developmental benefits, the research also identifies risks of psychological fatigue and diminished family engagement. The findings contribute to the scientific discourse by providing contextualized insights into how full day school affects the socio-psychological dynamics of a generation growing up in the digital era, emphasizing the need for balanced program design to sustain student well-being.